Rejection of the intestinal parasite Nippostrongylus brasiliensis by mast cell-deficient W/Wv anemic mice. - Crowle, P K (1981)
The ability of W/Wv anemic mice to accumulate mucosal mast cells and to reject the intestinal parasite Nippostrongylus brasiliensis was examined. W/Wv mice did not accumulate mucosal mast cells in response to infections with N. brasiliensis. They eliminated a primary infection more slowly than did their normal littermate controls but were as refractory as controls to second and third infections. W/Wv mice had higher serum titers of worm-specific immunoglobulin E than did controls. These results indicate that mucosal mast cells are not an absolute requirement for N. brasiliensis rejection.